Social and individual risk factors of alcohol and drug use among emerging adults in a nightlife setting - Antonina CONTINO; Marco CODARIN; Umberto ALBERT; Francesco MARCATTO; Stefano PASSINI; Thomas WEST; Lorenzo SILVESTRI; Lisa DI BLAS (Journal of Health and Social Sciences, 2025)
Introduction: Regular alcohol consumption, binge drinking, and the use of psychoactive drugs reach their peak in emerging adulthood. Among other factors, socialization contexts such as nightlife and individual differences in personality and motives for drug use contribute to adolescents’ exposure to risk. Methods: The current overnight project study was conducted in a summer nightlife setting. Italian adolescents aged 18 to 25 were invited to complete a short online survey about their lifetime, i.e., if ever used a substance, and past-month alcohol and drug use. A subsample also self-reported on a short Big Five personality measure, and another subsample on a measure of motives for drug use and perceived drug use among siblings and friends. A total of 770 people (54.8% females) provided valid self-reports. Results: The prevalence of binge drinking, frequent alcohol use, stimulants, and club drugs use was higher in the nightlife sample compared to a normative sample, with significant odds ratios indicating moderate to high risk, particularly for the male nightlife population. The Big Five personality profiles helped distinguish between frequent alcohol use and binge drinking, between regular cannabis use and use of other drugs, including poly-drug use. In the case of stimulant use, socially oriented motives predominated, while in the case of regular cannabis use and poly-drug use in the past month, self-related motives such as coping with anxiety also emerged. Finally, drug users were 2 to 4 times more likely than their peers to report substance use among their friends. Discussion: To date, no studies have been conducted in nightlife settings in Italy. The results of the present Overnight project confirm that the nightlife environment represents a risk factor for alcohol and substance use, and that personality and motives for substance use help identify young people at higher risk for substance misuse. Prevention projects can benefit from these findings.